Performance-Based Evaluation of Large Steel-Framed Structures in the Overall Fire Process - Guoqing Zhu; Guowei Zhang; Guanglin Yuan; Qingtao Li (Journal of Applied Mathematics)
This paper proposes a systematic analysis of fire hazards within an oversized steel-framed building that is taller and wider than usual, using a performance-based approach. We put forth both the method and the performance criteria for performance-based fire design of oversized steel-framed buildings and quantitatively evaluate the hazard factors (smoke temperature, smoke visibility, smoke toxicity, and structural collapse) in fire condition. FDS large eddy simulation and a modified temperature rise model of oversized steel structures were proposed for the quantitative analysis of hazard factors. Furthermore, we also studied evacuation process from oversized buildings and found that the Pathfinder model (developed based on water conservation model and behavior model) can accurately predict the evacuation process from oversized buildings based on our experimental study of an evacuation from a stadium. By comparing the time of occurrence of fire hazard factors (smoke temperature, smoke visibility, smoke toxicity, and structural collapse) and the time needed for safe evacuation, we could conduct a quantitative fire risk assessment on personal evacuation. And the time of occurrence of fire hazard factors can also provide a theoretical reference for emergency rescuers.